Conflict-Driven Constraint Answer Set Solving with Lazy Nogood Generation - Drescher, Christian; Walsh, Toby (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
We present a new approach to enhancing answer set programming (ASP) with constraint programming (CP) techniques based on conflict-driven learning and lazy nogood generation.